Axial Stability Exercises with Varying Back Muscle Contractions and Their Significant Impacts on Physiological Indicators due to Sports Technology and the Explosive Ability of Volleyball Players - Noori, Jian Abdullah (Indonesian Journal Publisher, 2024)
The current paper aimed to prepare axial stability exercises with a variety of back muscle contractions for volleyball players, and identify their important effects on some physiological indicators according to sports technology and the explosive ability of volleyball players. The research was based on two hypotheses, both of which indicated statistically significant variations in test results. Pre and post brain signals (EEG) for the three beta brain waves in the experimental group. There are statistically significant variations between the before and post-test findings for the explosive ability of the legs in the experimental group participants. The experimental research technique was used by creating one experimental group. The research population was represented by 12 young volleyball players from Al-Kahraba Club, who were selected using a comprehensive enumeration method to represent their community of origin, with a 100% representation of their community of origin in the sample for the 2023/2024 sports season. The latest sports technologies were employed to measure brain signals (EEG) for the three beta brain waves. This method is easy to apply on the volleyball court and does not require the transportation of players to other laboratories, as is the case with the (Neurosky) device, which includes a sensitive head kit. The Sarget test is approved for the purpose of measuring the explosiveness of the legs, and the EEG is equipped with NeuroSky technology to detect nerve signals. The exercises were prepared and applied in the research experiment by applying pre-tests on 8/10/2023 and then applying axial stability exercises with varying back muscle contractions for the period from 8/13/2023 until 10/5/2023. Applying post-tests on 8/10/2023 concluded the experiment, and the SPSS system statistically processed the collected data, leading to the conclusions and applications that axial stability exercises with varying back muscle contractions enhance the level of low beta EEG signals. To improve volleyball players' explosive abilities, coaches should prioritize physiological (EEG) signals measurement in line with their sports technology. Mobile balance tools used in axial stability training should be suitable for the players' abilities and ensure their safety from sudden falls or injuries.